The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.nurt.2009.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Vagus Nerve Stimulation in the Treatment of Refractory Epilepsy

Abstract: Summary: Many patients with epilepsy suffer from persistent seizures despite maximal anti-epileptic drug therapy. Chronic, intermittent vagus nerve stimulation has been proven to be an effective option for many patients suffering from refractory seizures who are not candidates for surgical resection. Although only a small minority of patients will be entirely seizure-free, vagus nerve stimulation, as an adjunct to medical therapy, may result in significant improvements in quality of life. Vagus nerve stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 106 publications
0
41
0
1
Order By: Relevance
“…The VNS delivers stimulation at set intervals, with adjustable factors, such as stimulation on-time, stimulation off-time, output current, frequency, and pulse width. 18 The generator typically provides a 0.5-millisecond pulse repeated at 10-30 Hz for 30 sec, every 150 to 300 seconds. 2 The current output is incrementally increased by 0.25 mA to 0.5 mA every 2 to 4 weeks according to the patient's response, until the optimum current output for stimulation is attained.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The VNS delivers stimulation at set intervals, with adjustable factors, such as stimulation on-time, stimulation off-time, output current, frequency, and pulse width. 18 The generator typically provides a 0.5-millisecond pulse repeated at 10-30 Hz for 30 sec, every 150 to 300 seconds. 2 The current output is incrementally increased by 0.25 mA to 0.5 mA every 2 to 4 weeks according to the patient's response, until the optimum current output for stimulation is attained.…”
Section: Methodsmentioning
confidence: 99%
“…2 The current output is incrementally increased by 0.25 mA to 0.5 mA every 2 to 4 weeks according to the patient's response, until the optimum current output for stimulation is attained. 18 A programming wand that communicates with the generator using radio frequency signals can be used to vary the output current, frequency, pulse width, and stimulation off and on time. 2 Additionally, a 50 gauss bar magnet provided by the manufacturer was reported in 8 studies [4][5][6][7]10,[14][15][16] and oxygen saturation was reported in 6.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations